2016
DOI: 10.1007/s00540-016-2290-2
|View full text |Cite
|
Sign up to set email alerts
|

New surgical scoring system to predict postoperative mortality

Abstract: PurposeThere is still no easy and highly useful method to comprehensively assess both preoperative and intraoperative patient statuses to predict postoperative outcomes. We attempted to develop a new scoring system that would enable a comprehensive assessment of preoperative and intraoperative patient statuses instantly at the end of anesthesia, predicting postoperative mortality.MethodsThe study included 32,555 patients who underwent surgery under general or regional anesthesia from 2008 to 2012. From the ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 23 publications
(21 reference statements)
4
18
0
4
Order By: Relevance
“…Er besteht aus den 3 Variablen intraoperativer Blutverlust, intraoperativer Blutdruck und Herzfrequenz während der OP (0-10 Punkte, 10 Punkte bedeuten geringstes Risiko [59]). Eine Reduktion des Scorewerts um je 2 Punkte war in einer klinischen Studie mit einem Anstieg des Mortalitätsrisikos jeweils um den Faktor 3,65 verbunden [60]. Die prädiktive Kraft dieses Scores ist lediglich moderat (über die "Area under the receiver operating characteristic curve" [AUROC] zwischen 0,63 und 0,81 [60][61][62]).…”
Section: Merkeunclassified
See 1 more Smart Citation
“…Er besteht aus den 3 Variablen intraoperativer Blutverlust, intraoperativer Blutdruck und Herzfrequenz während der OP (0-10 Punkte, 10 Punkte bedeuten geringstes Risiko [59]). Eine Reduktion des Scorewerts um je 2 Punkte war in einer klinischen Studie mit einem Anstieg des Mortalitätsrisikos jeweils um den Faktor 3,65 verbunden [60]. Die prädiktive Kraft dieses Scores ist lediglich moderat (über die "Area under the receiver operating characteristic curve" [AUROC] zwischen 0,63 und 0,81 [60][61][62]).…”
Section: Merkeunclassified
“…Eine Reduktion des Scorewerts um je 2 Punkte war in einer klinischen Studie mit einem Anstieg des Mortalitätsrisikos jeweils um den Faktor 3,65 verbunden [60]. Die prädiktive Kraft dieses Scores ist lediglich moderat (über die "Area under the receiver operating characteristic curve" [AUROC] zwischen 0,63 und 0,81 [60][61][62]). Interessanterweise soll sie durch Kombination mit dem üblichen ASA-Score als "SASA" zu steigern sein (AUROC 0,714-0,87, p < 0,001 [60,62])allerdings wird die Diskriminierung insbesondere bei Notfall-und Hochrisikoeingriffen kritisch beurteilt [61].…”
Section: Merkeunclassified
“…It has been shown that compared with the surgical risk scores only based on preoperative risk factors, the models including intraoperative risk factors, such as the Surgical Apgar Score and Surgical Risk Score, can improve the predictive ability for postoperative complications and mortality. 5,6 Second, this study only evaluated the associations of the ASA status classification and ICU utilization with 30-day postoperative mortality, but did not determine the performances of the two factors in predicting postoperative mortality. To determine predictive ability of two factors for postoperative mortality, after multivariate analysis, the authors should further construct the receiver operating characteristic curve and carry out sensitivity analysis to obtain the sensitivity, specificity, and positive and negative predictive values of the ASA status classification and ICU utilization for postoperative mortality in the validation and development sets.…”
Section: Dear Editormentioning
confidence: 99%
“…2 As compared with the surgical risk score only based on preoperative factors, moreover, the models combining preoperative and intraoperative risk factors can provide the improved predictive ability for postoperative morbidity and mortality. 6,7 Finally, in this study, the use of the same risk score to predict postoperative complications and mortality is not a suitable consideration. In fact, severe postoperative complications, such as acute kidney injury, sepsis, myocardial infarction, stroke, and pulmonary complications, have been significantly associated with short-term mortality after emergency surgery.…”
mentioning
confidence: 94%